Size Controlled Synthesis of Germanium Nanocrystals: Effect of Ge Precursor and Hydride Reducing Agent. (19th May 2015) - Carolan, Darragh; Doyle, Hugh
Abstract : Germanium nanocrystals (Ge NCs) have attracted increasing attention as a promising alternative to II–VI and IV–VI semiconductor materials as they are cheap, "green, " electrochemically stable, and compatible with existing CMOS processing methods. Germanium is a particularly attractive material for optoelectronic applications as it combines a narrow band gap with high carrier mobilities and a large exciton Bohr radius. Solution-phase synthesis and characterisation of size monodisperse alkyl-terminated Ge NCs are demonstrated. Ge NCs were synthesised under inert atmospheric conditions via the reduction of Ge halide salts (GeX4 ) by hydride reducing agents within inverse micelles. Regulation of NC size is achieved by variation of germanium precursor and the strength of hydride reducing agents used. UV-Visible absorbance and photoluminescence spectroscopy showed strong significant quantum confinement effects, with moderate absorption in the UV spectral range, and strong emission in the violet with a marked dependence on excitation wavelength.